Vocabulary Learning Strategies of Malaysian Chinese ESL Tertiary Learners - Tuluhong, (2006)
Language learners at all level use strategies. Effective use of learning strategies leads to more effective language learning. Though much research has been done in field of ESL, studies of vocabulary learning strategies are still a new area of ESL research in Malaysia. The purpose of this study is to describe the vocabulary learning strategies of proficient and less proficient Malaysian Chinese ESL tertiary learners. Two hundred and twenty-three Chinese students from thirteen Faculties at Universiti Putra Malaysia were involved in this study. A questionnaire of Vocabulary Learning Strategies and a semi-structured interview were used to collect the data. The interviews were audio taped. Data was analyzed quantitatively using the Statistical Package for Social Science. The interview data was analyzed qualitatively by identifying patterns in the responses. The analysis revealed that Malaysian Chinese ESL learners do make use of a variety of learning strategies in English vocabulary learning. Learners most actively use meta-cognitive strategies, such as use of English language media (internet, newspaper, TV etc.). Cognitive and memory strategies are also actively used in learning English vocabulary. However, social strategies are the least used strategies type. In learning English vocabulary, Chinese ESL learners commonly use English-language internet, take note in/out of class, guess from textual context in reading, use a bilingual dictionary and use English-language media. Both proficient and less proficient Chinese ESL learners most actively use more meta-cognitive strategies while least actively use social strategies. In addition, less proficient learners use a less number of strategies in learning English vocabulary. Factors that affecting choice of Chinese ESL learners’ vocabulary learning strategies are learner’ proficiency level, gender, age, programme (major) that learners enrolled in, and their first language. This study has provided an understanding of Malaysian Chinese students’ vocabulary learning strategies. It has also shown that Malaysian ESL Chinese learners do not use the same type of vocabulary learning strategies as other Chinese ESL learners in China or Taiwan.